Malaria Parasites Distribute Subversive Messages across Enemy Lines. Issue 1 (January 2017) - Rivkin, Anna; Ben-Hur, Sharon; Regev-Rudzki, Neta
Abstract : During its life cycle, the malaria parasite must cope with a set of diverse environments and institute strategies to alter its host's responses. A recent study remarkably demonstrates how these parasites exploit red blood cell products, loading them into 'armed' secreted vesicles sent to manipulate their host's 'endothelium battlefront', thereby promoting malaria infection.